A comparative study of biomass integrated gasification combined cycle power systems: Performance analysis. (May 2018) - Zang, Guiyan; Tejasvi, Sharma; Ratner, Albert; Lora, Electo Silva
Highlights: Eight BIGCC power systems schemes are simulated by using Aspen Plus software. The exergy efficiency of these systems ranges from 22.3% to 37.1%. Air gasification and externally fired gas turbine are preferred for systems without CO2 removal. Selexol is a preferred CO2 capture method due to its relatively low exergy destruction. Sensitivity analysis was conducted to provide more details of the exergy efficiency variation. Abstract: The Biomass Integrated Gasification Combined Cycle (BIGCC) power system is believed to potentially be a highly efficient way to utilize biomass to generate power. However, there is no comparative study of BIGCC systems that examines all the latest improvements for gasification agents, gas turbine combustion methods, and CO2 Capture and Storage options. This study examines the impact of recent advancements on BIGCC performance through exergy analysis using Aspen Plus. Results show that the exergy efficiency of these systems is ranged from 22.3% to 37.1%. Furthermore, exergy analysis indicates that the gas turbine with external combustion has relatively high exergy efficiency, and Selexol CO2 removal method has low exergy destruction. Moreover, the sensitivity analysis shows that the system exergy efficiency is more sensitive to the initial temperature and pressure ratio of the gas turbine, whereas has a relatively weak dependence on the initial temperature and initial pressure of the steam turbine.